Efektivitas Metode Ummi dalam Meningkatkan Kemampuan Membaca Al-Qur’an di Pondok Pesantren Week End Fatimah Ar Royyan Jongkang Buran Tasikmadu - Alamsyah, Imaniar Risty (Cetta: Jurnal Ilmu Pendidikan, 2025)
Reading and teaching the Koran is a practice that can make a Muslim the best among other Muslim brothers. Apart from getting good rewards, reading the Qur'an is also a source of comfort and guidance for Muslims in living their lives. The Fatimah Ar Royyan week end Islamic boarding school is the only boarding school that implements the week end system in Buran Tasikmadu Karanganyar, uses the Ummi method in learning the Al-Qur'an and has students from various age groups. The aim of this research is to find out how to implement, effectiveness, advantages and disadvantages in improving the ability to read the Al-Qur'an at the Fatimah Ar Royyan Islamic boarding school. The research method used is descriptive research with a qualitative approach using field research. Research results (1) In implementing the Ummi method at the Fatimah Ar Royyan weekend Islamic boarding school, 7 stages have been determined by the Ummi Foundation, namely; opening, apperception, concept planting. Concept understanding, practice, evaluation, closing. (2) by attending the Fatimah Ar Royyan week end Islamic boarding school using the ummi method, the students experienced good progress in reading the Al-Qur'an. (3) The advantages and disadvantages of applying the Ummi method are; systematic and structured, and easy to implement (advantages), the time required is relatively long (disadvantages).